The Effect of Compensation, Workload, and Work Life Balance on Turnover Intention - Ade Ainul Yaqin; Rhian Indradewa (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Turnover intention is a significant issue for many companies, especially in the telecommunications industry. Factors such as compensation, workload, and work-life balance play a crucial role in shaping employees' job satisfaction and work motivation. This study aims to analyze the impact of these factors on turnover intention, which is mediated by job satisfaction and work motivation. The data analysis method used is Structural Equation Modeling (SEM) SmartPLS, with the distribution of questionnaires to 210 employees with permanent employment status and job positions ranging from staff to leader/supervisor. The findings of this study support the 17 hypotheses proposed and show that compensation, workload, and work-life balance are related to turnover intention, and that job satisfaction and work motivation can mediate the relationship between these factors and turnover intention. Suggestions for future research include expanding the scope by involving more industry sectors and considering other external factors that may affect turnover intention. The contribution of this research provides insights for companies to design policies that can enhance job satisfaction and work motivation, as well as reduce turnover intention through better management of compensation, workload, and work-life balance.